The REthinking Clinical Trials Program Retreat 2023: Creating Partnerships to Optimize Quality Cancer Care. - Beltran-Bless, Ana-Alicia; Clemons, Mark; Vandermeer, Lisa; El Emam, Khaled; Ng, Terry L.; McGee, Sharon; Awan, Arif Ali; Pond, Gregory; Renaud, Julie; Barton, Gwen; Hutton, Brian; Savard, Marie-France (Current Oncology, 2024)
Patients, families, healthcare providers and funders face multiple comparable treatment options without knowing which provides the best quality of care. As a step towards improving this, the REthinking Clinical Trials (REaCT) pragmatic trials program started in 2014 to break down many of the traditional barriers to performing clinical trials. However, until other innovative methodologies become widely used, the impact of this program will remain limited. These innovations include the incorporation of near equivalence analyses and the incorporation of artificial intelligence (AI) into clinical trial design. Near equivalence analyses allow for the comparison of different treatments (drug and non-drug) using quality of life, toxicity, cost-effectiveness, and pharmacokinetic/pharmacodynamic data. AI offers unique opportunities to maximize the information gleaned from clinical trials, reduces sample size estimates, and can potentially "rescue" poorly accruing trials. On 2 May 2023, the first REaCT international symposium took place to connect clinicians and scientists, set goals and identify future avenues for investigator-led clinical trials. Here, we summarize the topics presented at this meeting to promote sharing and support other similarly motivated groups to learn and share their experiences.